2015
DOI: 10.1152/jn.00163.2014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of robotically modulating kinematic variability on motor skill learning and motivation

Abstract: It is unclear how the variability of kinematic errors experienced during motor training affects skill retention and motivation. We used force fields produced by a haptic robot to modulate the kinematic errors of 30 healthy adults during a period of practice in a virtual simulation of golf putting. On day 1, participants became relatively skilled at putting to a near and far target by first practicing without force fields. On day 2, they warmed up at the task without force fields, then practiced with force fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 42 publications
7
55
1
Order By: Relevance
“…This decreased feeling of competence could have jeopardized the subjects motivation to perform the task, and therefore, negatively affect their learning outcomes (McAuley et al, 1989). This is in line with a recent study that found that robotically increasing kinematic errors did not improve learning of a golf putting task, but decreased motivation in a persistent way (Duarte and Reinkensmeyer, 2015). In a previous study, we found that the addition of random disturbing forces increased subjects effort during training (Marchal-Crespo et al, 2014b), and this increase in effort resulted in better motor learning.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This decreased feeling of competence could have jeopardized the subjects motivation to perform the task, and therefore, negatively affect their learning outcomes (McAuley et al, 1989). This is in line with a recent study that found that robotically increasing kinematic errors did not improve learning of a golf putting task, but decreased motivation in a persistent way (Duarte and Reinkensmeyer, 2015). In a previous study, we found that the addition of random disturbing forces increased subjects effort during training (Marchal-Crespo et al, 2014b), and this increase in effort resulted in better motor learning.…”
Section: Discussionsupporting
confidence: 79%
“…However, there are also studies that did not find a benefit from augmenting errors during training. Increasing velocity errors when learning a golf putting task had no detectable effect on task performance (Duarte and Reinkensmeyer, 2015). In fact, augmenting errors resulted in a decrease on perceived competence and satisfaction and a longterm decrease in motivation.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Motor variability due to variability in human kinematic parameters, e.g., force field adaptation, speed and trajectory, and motivational factors such as level of user engagement, arousal and feelings of competence, necessary for performing a motor task is an integral part of the motor learning process (Duarte and Reinkensmeyer, 2015;Úbeda et al, 2015;Edelman et al, 2019;Faller et al, 2019). Such variability does not necessarily represent noise contents only, but may potentially be a manifestation of motor and perceptual learning processes.…”
Section: Motor Learning Process and Brain Functionmentioning
confidence: 99%
“…A few studies have shown that error-augmentation or noise-like haptic disturbance may be just as beneficial as haptic assistance for learning path-following (Chen and Agrawal, 2013), pursuit tracking (Powell and O’Malley, 2012; Lee and Choi, 2014), and target-hitting tasks (Powell and O’Malley, 2012). It has also been shown that, for a golf putting task, while error augmentation had no effect on post-training performance, it did negatively impact motivation, both during and after training (Duarte and Reinkensmeyer, 2015). This is in contrast to one of Wei et al (2005) hypothesized benefits of artificial error augmentation.…”
Section: Introductionmentioning
confidence: 99%